2020
DOI: 10.28916/lsmb.4.9.2020.58
|View full text |Cite
|
Sign up to set email alerts
|

Cardamonin inhibits nitric oxide production modulated through NMDA receptor in LPS-induced SH-SY5Y cell in vitro model

Abstract: Background: Cardamonin is a naturally occurring chalcone from the Alpinia species. It is known to possess antioxidant and anti-inflammatory properties. Our previous studies have shown that cardamonin has antihyperalgesic and antiallodynic effects on CCI-induced neuropathic pain in mice. Although the evidence of the association between cardamonin and neuropathic pain has been reported in animal studies, specific targets using in vitro models are still lacking. Objectives/Methods: This study aims to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…TRPv1 and NMDA N2B receptors are the leading player underlying hyperalgesia and allodynia in neuropathic pain conditions (Carrasco et al, 2018;Chia et al, 2020). In addition, LPS could also induce changes in reactive oxidative stress (ROS), a similar condition observed in chemotherapy-induced and diabetic-induced neuropathic pain, as previously discussed (Chanchal et al, 2016;Kaswan et al, 2020). The utilisation of LPS in inducing neuropathic pain pathophysiology in vitro model has been considered comprehensive as it can induce an inflammatory response and alters the leading players of nociceptive pathways such as the ion channels and receptors.…”
Section: Lipopolysaccharides-induced Neuropathic Pain Conditionmentioning
confidence: 78%
See 1 more Smart Citation
“…TRPv1 and NMDA N2B receptors are the leading player underlying hyperalgesia and allodynia in neuropathic pain conditions (Carrasco et al, 2018;Chia et al, 2020). In addition, LPS could also induce changes in reactive oxidative stress (ROS), a similar condition observed in chemotherapy-induced and diabetic-induced neuropathic pain, as previously discussed (Chanchal et al, 2016;Kaswan et al, 2020). The utilisation of LPS in inducing neuropathic pain pathophysiology in vitro model has been considered comprehensive as it can induce an inflammatory response and alters the leading players of nociceptive pathways such as the ion channels and receptors.…”
Section: Lipopolysaccharides-induced Neuropathic Pain Conditionmentioning
confidence: 78%
“…Furthermore, the induction of neuropathic pain-like condition on SH-SY5Y cell culture has resulted in changes in the expression of inflammatory proteins and signalling molecules, namely TLR receptors, interleukins, NFκB and nitric oxide (Amine et al, 2021;Kaswan et al, 2020;Lawrimore & Crews, 2017). SH-SY5Y cells are also commonly co-cultured with microglial cell lines to study the neuron-glial interaction in chronic pain mechanisms (Anand et al, 2015;Pandur et al, 2018).…”
Section: Sh-sy5y Cellsmentioning
confidence: 99%
“…The multitargeting properties of cardamonin is the key to its therapeutic effects against chronic diseases. Previous studies have demonstrated that cardamonin elicits antihyperalgesic and antiallodynic effects in CCI-induced neuropathic pain mice model modulated via the opioidergic and glutamatergic pathways [ 11 , 47 , 48 ]. With this understanding, we are now further investigating the possible mechanism of action of cardamonin in neuropathic pain by evaluating the involvement of the serotonergic pathways in cardamonin’s ability to exert antihyperalgesic and antiallodynic properties.…”
Section: Discussionmentioning
confidence: 99%